Development of Augmented Reality for Children Book Lutung Kasarung - Frihandhika Permana; Rizdania Dermawi; Sherina Izzaty (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
Folklore needs to be preserved and developed to improve the nation's emotional intelligence, especially the emotional intelligence of elementary school students who are the nation's next generation. With current technological advances, it is possible to develop an ordinary folklore book into a more interesting folklore book with the addition of Augmented Reality technology in it. By using the System Development Life Cycle (SDLC) method, an Augmented Reality-based application can be created to be able to make Lutung Kasarung children's folklore books can be enjoyed by getting experience that is more than just reading ordinary physical books because there is Augmented Reality technology inside. This Augmented Reality technology has 100% accuracy if it meets the specified requirements, namely a distance of 45 centimeters and a height of 30 centimeters, and in testing at a distance of 50 centimeters, 55 centimeters, 60 centimeters, 65 centimeters with a height of 25 centimeters and 30 centimeters. In addition, with the AR Book, it is also expected to be able to introduce AR technology to both parents and children as an alternative to children's fairy tale books.